2011
DOI: 10.1111/j.1349-7006.2011.02010.x
|View full text |Cite
|
Sign up to set email alerts
|

Hedgehog signaling pathway as a therapeutic target in various types of cancer

Abstract: Hedgehog (Hh) signaling is an important factor in growth and patterning during embryonic development. A mutation in Patched, Smoothened or Gli1, which regulate the Hh signaling pathway, might lead to the onset of glioblastoma, basal cell carcinoma, medulloblastoma and rhabdomyosarcoma. Recently, Hh signaling has been reported to be activated in a ligand‐dependent manner, contributing to carcinogenesis and cancer progression. Hedgehog signaling is reactivated in various types of cancer, and this contributes to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(60 citation statements)
references
References 76 publications
0
58
0
1
Order By: Relevance
“…HH signaling in cancer Three major cancers have been identified that involve cell-autonomous hedgehog (HH) pathway over-activation: medulloblastoma (MB), rhabdomyosarcoma (RMS) and basal cell carcinoma (BCC) (Ng and Curran, 2011). Whereas BCC likely can arise from multiple adult skin stem cells gone rogue under the influence of aberrant HH (Wong and Reiter, 2011;Youssef et al, 2010), the other two cancer types have embryonic origins and are triggered by developmental defects in HH signaling (Onishi and Katano, 2011). The SHH subtype of MB, a highly prevalent childhood brain tumor originating in the cerebellum, is characterized by activation of the HH pathway, which accounts for one quarter of all MB cases (Remke et al, 2013).…”
Section: Teethmentioning
confidence: 99%
“…HH signaling in cancer Three major cancers have been identified that involve cell-autonomous hedgehog (HH) pathway over-activation: medulloblastoma (MB), rhabdomyosarcoma (RMS) and basal cell carcinoma (BCC) (Ng and Curran, 2011). Whereas BCC likely can arise from multiple adult skin stem cells gone rogue under the influence of aberrant HH (Wong and Reiter, 2011;Youssef et al, 2010), the other two cancer types have embryonic origins and are triggered by developmental defects in HH signaling (Onishi and Katano, 2011). The SHH subtype of MB, a highly prevalent childhood brain tumor originating in the cerebellum, is characterized by activation of the HH pathway, which accounts for one quarter of all MB cases (Remke et al, 2013).…”
Section: Teethmentioning
confidence: 99%
“…Ectopic activation of the Hedgehog (HH) signaling pathway has been demonstrated to be involved in the initiation as well as the progression of prostate malignancy (3,6). The HH signaling pathway was first identified in Drosophila as a central organizer for proper embryonic patterning and development.…”
Section: Introductionmentioning
confidence: 99%
“…Although no physiologic SMO inhibitors have been identified so far, efforts to inhibit Hh pathway have been focused on this protein, considered the most druggable target of the pathway (38).…”
Section: Discussionmentioning
confidence: 99%